Respuesta :
Answer:
a) The recursion formula is [tex]R_n = R_{n-1}+n[/tex].
b) [tex]R_n = 1 + \frac{n(n+1)}{2}[/tex].
Step-by-step explanation:
a) Let us explore the recurrence. A plane with only one line is divided in two regions, so [tex]R_1 = 2[/tex]. If we add another line under the restrictions of the problem, [tex]R_2 = 4[/tex].
Notice that each line intersects the other n-1 lines, because there are no parallel lines. Assume we have n-1 lines and [tex]R_{n-1}[/tex] regions in the plane. If we add a new one we will have the previous [tex]R_{n-1}[/tex] plus n new regions. Because, for each line crossed by the new one there are a new region. Therefore,
[tex]R_n = R_{n-1}+n[/tex].
b) The method here is to develop the recurrence and find some pattern. Hence, using the formula for [tex]R_n[/tex], [tex]R_{n-1}[/tex] and [tex]R_{n-2}[/tex] we obtain
[tex]R_n = R_{n-1}+n=R_{n-2} + (n-1) + n = R_{n-3}+(n-2) + (n-1) + n.[/tex]
Notice that for each step back in the recurrence we add a new term in th sum. If we repeat the procedure n-1 times we will have
[tex]R_n = R_{n-3}+(n-2) + (n-1) + n = R_1 + 2+3+\cdots+(n-2) + (n-1) + n.[/tex]
Using that [tex]R_1 = 2[/tex]:
[tex]R_n = R_1 + 2+3+\cdots+(n-2) + (n-1) + n = 2 +2+3+\cdots+(n-2) + (n-1) + n.[/tex]
Here the smart step is to split the first 2 in 1+1, in order to obtain the sum of the first n natural numbers, and the expression for this last sum it is well known. Therefore,
[tex]R_n = 1 +(1+2+\cdots+ (n-1) + n) = 1+\frac{n(n+1)}{2}.[/tex]